2003
DOI: 10.1159/000069964
|View full text |Cite
|
Sign up to set email alerts
|

Tinea capitis in Brussels: Epidemiology and New Management Strategy

Abstract: Background: We found pre-established directives inadequate to cope with the current increase in anthropophilic tinea capitis in Brussels. Objectives: To study new epidemiological profiles and to define new strategies for management and prevention. Patients and Methods: A total of 122 children affected by tinea capitis were followed in our department from October 1, 2001, until September 30, 2002. The results were assessed retrospectively. Results: Anthropophilic tinea capitis represented 89.34% of the cases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 5 publications
3
20
2
Order By: Relevance
“…violaceum (18 %) and T. tonsurans (3 %) [75]. The same species were recorded by Detandt et al in a survey conducted in Brussels schools and nurseries over a 2-year period [76].…”
Section: Increase In Anthropophilic Dermatophytes Causing Tc In Europesupporting
confidence: 69%
“…violaceum (18 %) and T. tonsurans (3 %) [75]. The same species were recorded by Detandt et al in a survey conducted in Brussels schools and nurseries over a 2-year period [76].…”
Section: Increase In Anthropophilic Dermatophytes Causing Tc In Europesupporting
confidence: 69%
“…Nevertheless, there appears to be a shift towards the predominance of anthropophilic tineas in Europe, particularly in urban areas with much immigration (mainly from Africa) 1,6,13,25 . There has been a notable increase in cases due to T. tonsurans , as is evident in countries such as UK, 5 Ireland 5 or Netherlands and in cities such as Paris, 6 and even in a prospective study carried out in schools in Madrid 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Affected patients were of Mediterranean, Australian Aboriginal, or Ethiopian origin (23). More recently, studies from Sweden, Finland, and Belgium have also reported isolation of T. violaceum and T. soudanense from children with tinea capitis, most of whom were African (particularly Somali) immigrants (12,13,17).…”
Section: Discussionmentioning
confidence: 99%